ANTIHYPERTENSIVE DRUG TREATMENT DISCONTINUATION IN PATIENTS UNDERGOING ORTHOPEDIC SURGERY. IS IT SAFE?. (June 2018) - Koutsaki, M.; Kallistratos, M.; Soulioti, E.; Poulimenos, L.; Thomopoulos, C.; Mela, A.; Batistaki, C.; Chatziagelaki, E.; Achimastos, A.; Koutsaki, S.; Manolis, A.J.
Abstract : Objective: High blood pressure levels represent a common reason for postponing a scheduled surgery and are usually based on in hospital blood pressure (BP) measurements. Stress and anxiety of surgery represents a significant factor that can influence BP levels. To confront office BP levels in the perioperative clinic with ambulatory BP (ABPM) measurement as well as cortisol levels, in order to evaluate the influence of stress and anxiety on BP levels, as well as to assess the variability of BP during surgery. Design and method: This was a prospective observational study enrolled 45 subjects underwent to a scheduled knee surgery. In all patients' office BP (1 day before surgery), ABMP (12 hours before and 12 hours after surgery as well as plasma cortisol levels (1 hour before and 24 hours after surgery) were measured. In addition the magnitude of pain experienced before and after surgery was assessed by a questionnaire. In all patients, antihypertensive drug treatment was interrupted before surgery. Results: Forty five patients with mean age 73.8 ± 7.3 years were assessed. Mean office systolic BP (SBP) (138 ± 18 mmHg) while SBP at ABPM measurements 4 hours before, just before, during and just after the operation were (133 ± 18 mmHg p < 0.001, 136 ± 20 mmHg p < 0.05, 129 ± 19 mmHg p < 0.005 and 126 ± 24 mmHg mmHg p < 0.05 respectively) despite antihypertensive treatment discontinuation and despite the fact that pain as assessed by pain scale was greater after than before the operation (6.95 ± 2.2 vs 6.34 ± 2 p < 0.05). In addition, cortisol levels decreased significantly postoperatively as compared with operatively measures (10.3 ± 3.6 mcg/dL vs 14.0 ± 4.8 mcg/dL, p < 0.001). Interestingly, preoperative high BP levels were not associated with increased BP levels perioperativelly (p = ns). Conclusions: Preoperative discontinuation of antihypertensive drug treatment was not resulted into an increase of BP perioperativelly. Stress as expressed by cortisol levels is a significant determinant of increased BP levels before the operation.